2017
DOI: 10.15406/jnmr.2017.06.00151
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles Formulation as a Targeting Drug Delivery System

Abstract: A great interest has been centered on the idea of replacing daily administration of a drug with delivery devices which release a constant effective dose to the target tissues via a controlled release mechanism. Many pharmaceutical investigations have been carried out to develop controlled release oral dosage forms that sustain drug release. A sustained release system is defined as one in which the drug is initially made available to the body in an amount sufficient to give a rapid onset of the desired therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Prepared ceftriaxone loaded chitosan microparticles successfully decrease the MIC [18][19] of the bacteria and hence have the potential to decrease associated toxicity.…”
Section: In-vitro Release Kineticsmentioning
confidence: 99%
“…Prepared ceftriaxone loaded chitosan microparticles successfully decrease the MIC [18][19] of the bacteria and hence have the potential to decrease associated toxicity.…”
Section: In-vitro Release Kineticsmentioning
confidence: 99%
“…It was reported that if the drug dissolves in the matrix in which dispersed, both matrix and partition control is possible. If drug has low solubility in the elution medium, partition control dominates and the release is zero order [38][39][40], that is; Q = K D Cs t / h…”
Section: The Embedded Matrix Principlementioning
confidence: 99%